2015
DOI: 10.1037/a0039276
|View full text |Cite
|
Sign up to set email alerts
|

Wanting to maximize the positive and minimize the negative: Implications for mixed affective experience in American and Chinese contexts.

Abstract: Previous studies have demonstrated that European Americans have fewer mixed affective experiences (i.e., are less likely to experience the bad with the good) compared to Chinese. In this paper, we argue that these cultural differences are due to “ideal affect,” or how people ideally want to feel. Specifically, we predict that people from individualistic cultures want to maximize positive and minimize negative affect more than people from collectivistic cultures, and as a result, they are less likely to actuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 108 publications
11
137
0
Order By: Relevance
“…Although across cultures, people wanted to feel more positive than negative, European Americans and Chinese Americans indeed wanted to feel positive affect (relative to negative affect) more than did Hong Kong and Beijing Chinese. These differences were also related to the relative value placed on independence vs. interdependence [26]. Maximizing positive and minimizing negative emotion facilitates differentiating oneself from others, which is a goal of independence; in contrast, balancing positive and negative facilitates attention and attunement to others, a goal of interdependence.…”
Section: Valuation (And Devaluation) Of Other Emotional Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although across cultures, people wanted to feel more positive than negative, European Americans and Chinese Americans indeed wanted to feel positive affect (relative to negative affect) more than did Hong Kong and Beijing Chinese. These differences were also related to the relative value placed on independence vs. interdependence [26]. Maximizing positive and minimizing negative emotion facilitates differentiating oneself from others, which is a goal of independence; in contrast, balancing positive and negative facilitates attention and attunement to others, a goal of interdependence.…”
Section: Valuation (And Devaluation) Of Other Emotional Statesmentioning
confidence: 99%
“…For instance, although there are differences in the degree to which cultures want to maximize positive and minimize negative affect, as described above, across cultures, the more people want to maximize the positive and minimize the negative, the less likely they are to actually experience positive and negative affect at the same time [26]. …”
Section: Links Between Ideal Affect and Momentary Actual Affective Exmentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, previous research demonstrated that cultural differences between East Asians and Americans in mixed emotions were more representative in pleasant emotional events (Hui et al, 2009; Leu et al, 2010; Sims et al, 2015). Also, cultural differences are considered to be more salient in pleasant than in unpleasant emotions (Leu et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Another challenge for Chinese students is that Chinese culture does not praise openness or self-expression whereas American culture does. These differences between Chinese and American cultures create a lot of frustration due to miscommunication and make it difficult for Chinese students to feel confident when communicating with Americans (Sims, et al, 2015).…”
Section: Challenges Encountered By Chinese Students In the Us Univementioning
confidence: 99%